2007
DOI: 10.1177/0093854806290162
|View full text |Cite
|
Sign up to set email alerts
|

Development and Field Test of a Gender-Informed Security Reclassification Scale for Female Offenders

Abstract: Two samples of Canadian federal female offender case files are used to develop and test a gender-informed security reclassification scale. Study 1 uses 285 consecutive offender security level (OSL) reviews for federally sentenced women to empirically construct the Security Reclassification Scale for Women (SRSW). Study 2 uses all federal female OSL reviews that occurred between July 2000 and June 2003 ( n = 580) to test the validity and reliability of the SRSW. Results suggest that the SRSW is a reliable and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
0
28
1
Order By: Relevance
“…The challenge may be to empirically and pragmatically conduct validation studies on gender-specific risk assessment tools as well as gender-neutral risk tools. Research in this area has already begun with the development of the Security Reclassification Scale for Women in Canada (SRSW; Blanchette & Taylor, 2005), the Women's Risk Need Assessment in the US (WRNA; Van Voorhis, Salisbury, Wright, & Bauman, 2008) and the publication of the Female Additional Guidelines (FAM) for the HCR-20 (De Vogel et al, 2012). The task will now be for researchers to demonstrate the predictive validity of such tools.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…The challenge may be to empirically and pragmatically conduct validation studies on gender-specific risk assessment tools as well as gender-neutral risk tools. Research in this area has already begun with the development of the Security Reclassification Scale for Women in Canada (SRSW; Blanchette & Taylor, 2005), the Women's Risk Need Assessment in the US (WRNA; Van Voorhis, Salisbury, Wright, & Bauman, 2008) and the publication of the Female Additional Guidelines (FAM) for the HCR-20 (De Vogel et al, 2012). The task will now be for researchers to demonstrate the predictive validity of such tools.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…In support, a meta-analysis that sampled a much smaller number of studies found that the factors enumerated above predicted new offenses and other adverse outcomes for women (Dowden & Andrews, 1999). Additional studies have found the dynamic risk assessment instruments to be valid for women (Andrews, Dowden, & Rettinger, 2001;Blanchette & Brown, 2006;Coulson, Ilacqua, Nutbrown, Giulekas, & Cudjoe, 1996;Holsinger, Lowenkamp, & Latessa, 2003), but others reported areas of divergence (Blanchette, 2005;Law, Sullivan, & Goggin, in press;Olson, Alderden, & Lurigio, 2003;Reisig et al, 2006). It is noteworthy, however, that few studies speak directly to the recommendations from the gender-responsive literature.…”
mentioning
confidence: 98%
“…Canada has historically led the way in the development of offender assessment. In line with this trend, recent research by Blanchette and Taylor (2007) used samples of Canadian federal female offender case‐files to develop a gender‐informed risk assessment scale. Beginning with a large range of potential risk predictors, the researchers used regression analyses to identify the best predictors of risk.…”
Section: Developments In the Assessment Of Women's Need And Riskmentioning
confidence: 99%